A Review on the Biodiversity and Biogeography of Toxigenic Benthic Marine Dinoflagellates of the Coasts of Latin America - Durán-Riveroll, Lorena María; Cembella, Allan D.; Okolodkov, Yuri B. (Frontiers in Marine Science, 2019)
Many benthic dinoflagellates are known or suspected producers of lipophilic polyether phycotoxins, particularly in tropical and subtropical coastal zones. These toxins are responsible for diverse intoxication events of marine fauna and human consumers of seafood, but most notably in humans, they cause toxin syndromes known as diarrhetic shellfish poisoning (DSP) and ciguatera fish poisoning (CFP). This has led to enhanced but still insufficient efforts to describe benthic dinoflagellate taxa using morphological and molecular approaches. For example, recently published information on epibenthic dinoflagellates from Mexican coastal waters includes about 45 species from 15 genera, but many have been only tentatively identified to species level, with fewer still confirmed by molecular criteria. This review on the biodiversity and biogeography of known or putatively toxigenic benthic species in Latin America restricts geographical scope to neritic zones of the North and South American continents, plus adjacent islands and coral reefs. The focus is on species from subtropical and tropical waters, primarily within the genera Prorocentrum, Gambierdiscus/Fukuyoa, Coolia, Ostreopsis and Amphidinium. The state of knowledge on reported taxa in these waters is inadequate and time-series data are generally lacking for prediction of regime shift and global change effects. Details of their respective toxigenicity and toxin composition have only recently been explored for a few locations. Nevertheless, by describing the specific ecosystem habitats for toxigenic benthic dinoflagellates, and comparing among three key regions - the Gulf of Mexico, Caribbean Sea and the subtropical and tropical Pacific coast, insights are generated for further risk assessment of global spreading of toxic benthic species and for the management of their effects in Latin America.